Reproducible preparation of spheroids of pancreatic hormone positive cells from human iPS cells: An in vitro study - Konagaya, Shuhei; Iwata, Hiroo (Biochimica et biophysica acta, 2016)
Transplantation of islets of Langerhans is regarded as a promising therapy for type 1 diabetes. A large number of β-cells are required for the treatment of human type 1 diabetes. Pluripotent stem cells, such as embryonic stem cells and induced pluripotent stem cells, have been considered as new sources for cell replacement therapy. Cell aggregates were prepared from human iPS cells using agarose microwell plates and differentiated into pancreatic endocrine cells by changing the culture media with different additives. After 20days of culture, approximately 30% of cells in aggregates were positive for C-peptide. After another 14days in culture, the cells gained an ability to alter C-peptide release in response to changes in the glucose concentration. Uniform aggregates of human iPSCs were easily prepared on agarose microwell plates and efficiently differentiated into the pancreatic endocrine lineage. Thus, aggregate culture is a suitable method for preparing islet-like aggregates from human iPSCs. Our results indicate that the microwell plate is suitable for scaling up the preparation of pancreatic endocrine cells from human iPS cells in a robotic system. •Uniform aggregates of human iPSCs were prepared on agarose microwell plates.•Human iPSCs were efficiently differentiated into the pancreatic endocrine lineage.•Aggregate culture is a suitable method for preparing islet-like aggregates from human iPSCs.